2021
DOI: 10.1055/s-0041-1728664
|View full text |Cite
|
Sign up to set email alerts
|

Protein C Gene Mutation in an Older Adult Patient with Clostridium perfringens Septicemia-Related Visceral Vein Thrombosis

Abstract: A 78-year-old Japanese male with Clostridium perfringens septicemia and cholecystitis was found to have thrombosis in the left branch of intrahepatic portal vein as well as superior mesenteric vein. Visceral vein thrombosis (VVT) in this case was associated with protein C deficiency, due to a heterozygous mutation, p. Arg185Met. Our experience emphasizes that VVT, or other thromboembolic events, may occur in later life, triggered by environmental thrombosis risk factors, together with underlying hereditary pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Clostridia (especially Clostridium di cile and Clostridium perfringens) were found to be associated with thrombotic events such as VTE, portal vein thrombosis, superior mesenteric vein thrombus, and visceral vein thrombosis [44][45][46][47][48]. Additionally, in vitro and animal studies have indicated that platelet endothelial cell adhesion molecule-1 (PECAM-1) plays a negative regulatory role in thrombus formation [49,50], while the binding of Clostridium perfringens βtoxin to PECAM-1 induces the formation of cellular membrane pores, thereby interfering with the function of PECAM-1 [51].…”
Section: Discussionmentioning
confidence: 99%
“…Clostridia (especially Clostridium di cile and Clostridium perfringens) were found to be associated with thrombotic events such as VTE, portal vein thrombosis, superior mesenteric vein thrombus, and visceral vein thrombosis [44][45][46][47][48]. Additionally, in vitro and animal studies have indicated that platelet endothelial cell adhesion molecule-1 (PECAM-1) plays a negative regulatory role in thrombus formation [49,50], while the binding of Clostridium perfringens βtoxin to PECAM-1 induces the formation of cellular membrane pores, thereby interfering with the function of PECAM-1 [51].…”
Section: Discussionmentioning
confidence: 99%